1990
DOI: 10.1007/bf02114402
|View full text |Cite
|
Sign up to set email alerts
|

Erythema nodosum and Hodgkin's disease

Abstract: Erythema nodosum is an unusual manifestation of Hodgkin's lymphoma. One patient with long remission of Hodgkin's disease manifested persistent erythema nodosum beginning one and three months before relapse was clinically evident. So, the diagnosis of Hodgkin's disease should be considered in patients with unexplained recurrent erythema nodosum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…In most cases EN preceded the occurrence of HD by 1–12 months; 4,5 , 7,11 , 13,14 however, it preceded HD by 24 months in one case, 12 and occurred 3 years after the diagnosis of the malignant disease in another 6 . Skin nodules developed rarely during the remission phases of of HD 8,10 . Leukocytoclastic vasculitis was associated in two cases 14…”
Section: Reportmentioning
confidence: 96%
See 1 more Smart Citation
“…In most cases EN preceded the occurrence of HD by 1–12 months; 4,5 , 7,11 , 13,14 however, it preceded HD by 24 months in one case, 12 and occurred 3 years after the diagnosis of the malignant disease in another 6 . Skin nodules developed rarely during the remission phases of of HD 8,10 . Leukocytoclastic vasculitis was associated in two cases 14…”
Section: Reportmentioning
confidence: 96%
“…Lymphomas can represent a rare cause of EN 1–3 . The first report of EN occurring as a manifestation of HD appeared in 1906 4 and 15 other cases have been reported in the literature 4–14 …”
Section: Reportmentioning
confidence: 99%
“…Therefore, drug-related was considered the most likely cause of EN, and the suspected drug was olaparib, which was started four days before onset. It was reported that the relapse of malignancy might induce EN, although the patient’s disease status was relatively stable in this case [ 16 ]. Erythema induratum of Bazin is included in the differential diagnosis of EN.…”
Section: Discussionmentioning
confidence: 81%
“…Patients did not respond to prednisone. Finally, in addition to long noted associations, erythema nodosum has recently been reported with Hodgkin's disease [66].…”
Section: Nonarticular Rheumatic Syndromesmentioning
confidence: 98%